Worth the weight? Post weigh-in rapid weight gain is not related to winning or losing in professional mixed martial arts - Kirk, C.; Langan-Evans, C.; Morton, J. P. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
Body mass (BM) manipulation via rapid weight loss (RWL) and rapid weight gain (RWG) is a common practice among mixed martial art (MMA) athletes to ensure qualification for the division in which the athlete wishes to compete. Professional MMA competitors in California are required to weigh in twice: 24 hr prior to competition and immediately prior to the bout after they have typically engaged in RWG. In analyzing data from five MMA events sanctioned by the Californian State Athletic Commission, the authors used Bayesian analyses to compare bout winners (n = 62) and losers (n = 62) in terms of in-competition BM (in kilograms) and the amount of BM regained between the two weigh-ins (in kilograms). These data do not support the hypothesis that differences in in-competition BM (Bayes factor [BF10] = 0.667, d = 0.23) or the amount of BM regained between the two weigh-ins (BF10 = 0.821, d = 0.23) determine winning or losing. In addition, there was no statistical difference between bouts ending via strikes, submission, or decision for either in-competition BM (BF10 = 0.686, Omega2 < 0.01) or the amount of BM regained between the two weigh-ins (BF10 = 0.732, Omega2 = 0.054). In conclusion, the authors report for the first time that the magnitude of RWG does not predict winning or losing in a professional cohort of MMA athletes. In addition, they also report that MMA athletes typically compete at a BM that is at least 1-2 divisions higher than the division in which they officially weighed-in. These analyses may provide impetus for governing bodies and coaches to enact changes at both professional and amateur levels to reduce negative health consequences associated with extreme RWL and RWG.